Student-Centered Curriculum Design through Social Media Engagement: Toward a Participatory Digital Learning Ecosystem - Zaenal Abisin; Ahmad Mustaqim (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Researchers on the role of student engagement in social media were building upon existing research to construct participatory curriculum in the digital learning habitat of higher education students. The paradigm employed for this study was Participatory Action Research and Design-Based Research, as the work included 30 undergraduate students for a six-week learning intervention. Data collection methods included digital ethnography, semi-structured interviews, as well as WhatsApp interactions and Discord analyses. Thematic analysis with NVivo yielded three themes: active engagement and peer initiative; co-construction of curriculum and salience of content; and challenges of digital learning. Thus, it follows that students had taken the initiative of starting intellectual discussions, as well as suggesting or co-constructing the content of the curriculum as a community endeavor. Their feedback directed the learning process to be student-centered and contextualized. Although these have been recognized as strengths, some of the challenges were observed in the form of digital fatigue, distraction from non-academic content, and differences in digital literacy. This study makes a contribution to theory by extending the participatory curriculum concept into digital community spaces and, more practically, developing a model that would include student voice in planning curricular stands through social media. The findings further suggest that when put to intentional use, social media might be a co-creation space to support inclusive, flexible, and reflexive curriculum development in a digital age.